A validated finite element analysis procedure for porous structures - Sergio Ruiz de Galarreta (Materials & Design, 2020)
Cellular materials are gaining interest thanks to developments in additive manufacturing. Whilst Finite Element Analysis (FEA) is commonly used to obtain the mechanical behaviour of these structures, different modelling and simulation methodologies are followed in literature. Consequently, there is not a clear procedure to accurately evaluate the mechanical properties of porous structures. This study presents a method to perform FEA of lattice structures with accurate results. All inputs required to simulate compression testing of lattices in FEA were investigated, these included the modelling type, element size, number of unit cells required, boundary conditions and the material model. The effect of these variables on the modulus and yield strength of a lattice structure was studied.Lattices with two unit cell structures, varying unit cell sizes and relative densities were additively manufactured in stainless steel, compression tested and compared to FE simulations. The material model for the FE simulations was obtained from tensile testing individual micro-struts of varying diameters. FE simulation results were in good agreement with the experimental results with an average error for the modulus and yield strength of ~10% and 17% respectively. The methodology presented should provide a foundation to accelerate development and adoption of these structures. Keywords: Lattice structures, Finite element analysis, Mechanical testing, Additive manufacturing, Struts